Culture Change and Affectionate Communication in China and the United States: Evidence From Google Digitized Books 1960–2008 - Wu, Michael Shengtao; Li, Boyuan; Zhu, Liangliang; Zhou, Chan (Frontiers in Psychology, 2019)
Humans are born with the ability and the need for affection, but communicating affection as a social behavior is historically bound. Based on the digitized books of Google Ngram Viewer from 1960 through 2008, the present research investigated the affectionate communication (AC) in China and in the US, and its changing landscape along with social changes from collectivist to individualistic environments. In particular, we analyzed the frequency in terms of verbal affection (e.g., love you, like you), non-verbal affection (e.g., hug, kiss), and individualism (indicated by the use of first-person singular pronouns, such as I, me, and myself) in Chinese and in American books. The results revealed a convergent increasing trend of AC over the past decades, although the frequency of affection words was lower in Chinese than in American books. Further, the individualism was found to be positively related to the frequency of affection words in both Chinese and American books. These results demonstrate the effect of cultural changes on AC, in that affection exchange becomes popular in adaptation to individualistic urban environments, which provide the evidence about the cross-cultural difference in love expression and the cultural universality of social change in Eastern and Western societies.